Vocabulary learning through extensive reading - Azizan, Nurizzati Asyimah (2013)
This study examined the effectiveness of two modes of vocabulary learning through extensive reading (ER) which are incidental vocabulary learning and intentional vocabulary learning. 20 participants (n=20) which are in the low-proficient English level were selected from one intact class through the method of convenient sampling. The participants were further divided into two groups, n=10 in the control group (incidental vocabulary learning) and n=10 in the experimental group (intentional vocabulary learning). Both groups sat on a pre-test to determine their vocabulary knowledge level. Then, the experimental group were given the intentional vocabulary learning treatment for five weeks. After five weeks, both groups sat on a post-test. The results show that there is a significant difference between the post-test mean scores of the control and experimental group with the p-value of 0.025 (p < 0.05). The experimental group scored significantly higher in post-test as compared to the control group. The data demonstrated that low-proficient learners will notice and learn more new words through intentional vocabulary learning as compared to incidental vocabulary learning.